THE USE OF TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION (TENS), PATELLAR MOBILIZATION, AND QUADRICEPS SETTING IN BILATERAL KNEE OSTEOARTHRITIS GRADE 2 CASE IN OLDER ADULTS - Pramaisella, Inggrid Pitaloka; Rahayu, Umi Budi (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Osteoarthritis (OA) is known as degenerative joint disease where there is joint abnormality causing inflammation involving cartilage and surrounding tissue which result in morbidity and functional limitations, especially for older adults. Method: The aim of the study was to determine the benefits of performing Transcutaneous Electrical Nerve Stimulation (TENS), Patellar Mobilization, and Quadriceps Setting in Bilateral Knee Osteoarthritis Grade 2 on Elderly. The assessment used was Numerical Rating Scale Pain Assessment (NRS), Manual Muscle Testing (MMT), and Western Ontario and McMaster Universities Osteoarthritis (WOMAC). Discussion: The giving of Patellar Mobilization is able to increase function in older adults and also decrease knee joint stiffness and pain, meanwhile the giving of Quadriceps Setting is also able to increase Quadriceps muscle strength, and the application of Transcutaneous Electrical Nerve Stimulation (TENS) is able to decrease pain caused by OA and increase physical performance in patient with Knee OA. Conclusion: After doing physiotherapy as many as 4 times using Transcutaneous Electrical Nerve Stimulation (TENS), Patellar Mobilization, and Quadriceps Setting, it is gained the decrease of pressure and movement pain, the increase of right and left leg muscle strength, and also the increase of WOMAC functional Test result after being given Transcutaneous Electrical Nerve Stimulation (TENS), Patellar Mobilization, and Quadriceps Setting.